E-learning and higher order thinking: Impact of STEM-based approach - Rahman, Abdul; Suharyat, Yayat; Santosa, Tomi Apra; Abdullah, Efendi; Rizal, Pahmi (Psychology, Evaluation, and Technology in Educational Research, 2023)
Please Many studies have described meta-analysis on the overall effect of e-learning influence in learning. However, there has been no meta-analysis of the overall effect of STEM-based e-learning on Higher Order Thinking Skills (HOTS). The purpose of this study investigates the effect of STEM-based e-learning on students' critical thinking skills in Indonesia. This type of research is a Systematic Literature Review (SL) and meta-analysis. Data sources came from 12 national and international journals published in 2018-2023. The process of searching for data sources through Google Scholar, ScienceDirect, Wiley, Eric, and Springer. Data analysis used the Hedge formula to calculate effect size with the help of the JSAP application. The findings show that the effect size value (ES = 0.84) is very high. This explains that STEM-based e-learning provides a very high positive impact and is effective in improving students' Higher Order Thinking Skills (HOTS). Furthermore, HOTS characteristics do not cause heterogeneity in the results of STEM-based e-learning research on students' Higher Order Thinking Skills. The findings suggest that educators should choose STEM-based e-learning as one of the learning models to improve students' Higher Order Thinking skills in Indonesia